IMPLEMENTASI SISTEM INFORMASI MANAJEMEN PENDIDIKAN DALAM MENINGKATKAN PELAYANAN ADMINISTRASI DI SEKOLAH MENENGAH PERTAMA ISLAM TERPADU CAHAYA ISLAM, BUARAN, SERPONG - Yayuk Yunita Sari; Yunus Yunus (STKIP Pesisir Selatan, 2026)
This study aims to determine the implementation of the Education Management Information System in improving administrative services at Cahaya Islam Integrated Islamic Junior High School (SMP IT), Buaran, Serpong. The background of this study is based on the demand for improving the quality of school administrative services in the digital era, where the management of educational data and information is required to be faster, more accurate, more effective, and more transparent. In practice, the education management information system is seen as capable of supporting school administrative activities through more integrated data management, more efficient services, and the provision of information that is more easily accessible to schools and stakeholders. This study uses a qualitative approach with a descriptive research type. Data collection techniques are carried out through observation, interviews, and documentation, while data analysis uses data reduction, data presentation, and drawing conclusions. Data validity is carried out through triangulation of sources and techniques, as is commonly used in research on the implementation of management information systems in schools. The results of the study indicate that the implementation of the Education Management Information System at Cahaya Islam Integrated Islamic Junior High School, Buaran, Serpong has made a positive contribution to school administrative services. The application of this system helps manage student, teacher, and academic administration data more orderly, accelerates the service process, facilitates information searches, and improves the work efficiency of administrative staff.